IMPLEMENTASI MANAJEMEN KURIKULUM INTEGRATIF-INTERKONEKTIF AGAMA DAN SAINS DI SMP MUHAMMADIYAH MERAUKE - Dani Nurcholis; Pulung Riyanto; Ade Yuni Sahruni; Febry Ramadhani Suradji; Ronny Brayntin Rahail (Jurnal Manajemen Pendidikan, 2025)
Curriculum planning must involve analyzing student needs, developing integrative core competencies, and determining collaborative learning strategies. During the implementation phase, teachers are required to creatively connect science concepts with Islamic values ​​in teaching and learning activities. This study aims to describe the implementation of integrative-interconnective curriculum management between religion and science at SMP Muhammadiyah Merauke. Using a descriptive qualitative method with interviews, observations, and documentation, the research involved the principal, Islamic education teachers, science teachers, and students. The findings reveal that curriculum planning explicitly integrates Islamic values into syllabi and lesson plans. Implementation demonstrates collaboration between religion and science teachers through contextual learning that enhances students’ motivation and scientific reasoning. Evaluation is conducted reflectively, although standardized instruments for assessing integrative outcomes are still lacking. Overall, the curriculum positively influences students’ character development and religious-scientific literacy. Sustainable implementation requires institutional support, integrative teaching materials, and cross-disciplinary teacher training.